Edukasi Dan Demonstrasi Pemanfaatan Biji Pepaya Untuk Pencegahan Cacingan Pada Anak Di Danukusuman Serengan Surakarta - Adhi Kumoro Setya; Dwi Haryatmi; Chalista Parastri; Dewi Lia Tri; Dinda Choirunissa (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Preschool and school age children are a high risk group for helminthiasis. Apart from that, school children are also a group that is vulnerable to inadequate nutrition and complaints of infection if helminth occur. Health problems and malnutrition in school-aged children will continue until adolescence. Danukusuman is an area in Surakarta that is densely populated and the residential conditions are vulnerable to rubbish, rivers and markets. In papaya fruit there is a karpain compound which has anti-microbial properties and is able to neutralize toxins. For the purpose of treating helminth such as roundworms, karpain works by coagulating albumin, thereby making the worms become weak, die and leave the sufferer's body. The objectives of this community service include; providing information about the types and dangers of helminthiasis in children, respondents can process papaya seeds into snacks, and additional nutrition as well as preventing helminthiasis in children, including reducing unhealthy snacks. Method This service activity is carried out using presentations at the counseling stage and demonstrations of making samples of processed papaya seed products as a solution to overcome health problems while improving skills for cadres and the community. As a result of this activity, 67 people succeeded in participating from the initial target of 50 people. The community was enthusiastic about the emergence of 9 questions, the knowledge test after the service received an average score of 84 (very good) and succeeded in trying to process papaya seeds into additional food products and anthelmintics.